Sendas perdidas de la razón: cuando "el sueño de la razón produce monstruos" (1996)
The author resorts to the Weber-Scheme, which explains rationality on the basis of an underlying religióses Weltbild (ascetic Protestantism in the case of Western rationality). In view of the crisis of Western rationality, the author asks himself what would happen if one would resort to some other religióses Weltbild, as for example Judaism, to face the great challenges of the Aufklarung. He then pleads for an anamnetische Vemunft, upheld by Spinoza (the "Marrano of reason") and the jewish-german philosophers H.Cohén, F.Rosenszweig and W.Benjamin.